Is prostate cancer screening cost‐effective? A microsimulation model of prostate‐specific antigen‐based screening for British Columbia, Canada. Issue 4 (4th February 2014) - Pataky, Reka; Gulati, Roman; Etzioni, Ruth; Black, Peter; Chi, Kim N.; Coldman, Andrew J.; Pickles, Tom; Tyldesley, Scott; Peacock, Stuart
<x xml:space="preserve">Abstract</x> Prostate‐specific antigen (PSA) screening for prostate cancer may reduce mortality, but it incurs considerable risk of over diagnosis and potential harm to quality of life. Our objective was to evaluate the cost‐effectiveness of PSA screening, with and without adjustment for quality of life, for the British Columbia (BC) population. We adapted an existing natural history model using BC incidence, treatment, cost and mortality patterns. The modeled mortality benefit of screening derives from a stage‐shift mechanism, assuming mortality reduction consistent with the European Study of Randomized Screening for Prostate Cancer. The model projected outcomes for 40‐year‐old men under 14 combinations of screening ages and frequencies. Cost and utility estimates were explored with deterministic sensitivity analysis. The incremental cost‐effectiveness of regular screening ranged from $36, 300/LYG, for screening every four years from ages 55 to 69 years, to $588, 300/LYG, for screening every two years from ages 40 to 74 years. The marginal benefits of increasing screening frequency to 2 years or starting screening at age 40 years were small and came at significant cost. After utility adjustment, all screening strategies resulted in a loss of quality‐adjusted life years (QALYs); however, this result was very sensitive to utility estimates. Plausible outcomes under a range of screening strategies inform discussion of prostate cancer screening policy in BC and similar jurisdictions. Screening may be cost‐effective, but the sensitivity of results to utility values suggests individual preferences for quality versus quantity of life should be a key consideration.